Automatic code generation for applications which run on common platforms - Baluja, Shumeet; Wilson, Eric; Bose, Suddhasattwa; Han, Hyosung (2003)
A method of automated code generation. The method includes identifying an event related to the execution of an application, generating code related to the event using an automated process, and integrating the code into the application. It is emphasized that this abstract is provided to comply with the rules requiring an abstract which will allow a searcher or other reader to quickly ascertain the subject matter of the technical disclosure. It is submitted with the understanding that it will not be used to interpret or limit the scope or the meaning of the claims.